Problem based learning in radiography education: A narrative review. Issue 2 (May 2021) - Lawal, O.; Ramlaul, A.; Murphy, F.
Abstract: Objectives: Radiography practice is fast developing with new imaging updates and challenging scenarios to deal with on a frequent basis. There is a need to equip students with the skill to be independent learners and develop critical thinking skills, so they can change their practice as the profession evolves. Problem Based Learning (PBL) has widely been adopted in medical and nursing training worldwide as a result of its desirable benefits. In order to ascertain the efficacy of the technique, this paper presents a review of the essential aspects of PBL, such as the theories, process, key roles and implication for radiography education and practice. Key findings: The use of a defined model provides a useful structure to the PBL exercise with the addition of reflection, which is a pertinent inclusion within the process. The role of the facilitator in PBL is significant to students' learning as they help guide the students to the learning outcomes and provide support to the group; however, their skills development is an important factor to consider in PBL. Conclusion: This teaching approach has key benefits in radiography education and training in particular, its impact on preparing students for autonomous clinical practice. Implications for practice: The application of PBL in developing students' critical thinking and decision-making abilities support the narrowing of the spoon-feeding expectation of students and render it a useful pedagogical implementation within radiography programmes.